2020
DOI: 10.21203/rs.2.18762/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential of Zymomonas mobilis as an electricity producer in ethanol production

Abstract: Background: Microbial fuel cell (MFC) convokes microorganism to convert biomass into electricity. However, most well-known electrogenic strains can not directly use glucose to produce valuable products. Zymomonas mobilis, a promising bacterium for ethanol production, owns special Entner-Doudoroff pathway with less ATP and biomass produced and the low energy-coupling respiration, making Z. mobilis a potential exoelectrogen. Results: A glucose-consumed MFC is constructed by inoculating Z. mobilis. The electricit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…On the other hand, for most non-electroactive organisms, due to the lack of electron transfer pathway, they are not able to directly deliver or uptake electrons, which severely limited their applications in anodic electro-fermentation or cathodic electro-fermentation. Although addition of redox mediators or surfactants could promote indirect EET and regenerate intracellular reduce equivalents [ 46 , 65 ], their inhibition on the cell growth would be hazard for practical applications. Lastly, to achieve efficient coupling of inward electrons with cell growth and metabolic pathways is a bottleneck in the development of EF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for most non-electroactive organisms, due to the lack of electron transfer pathway, they are not able to directly deliver or uptake electrons, which severely limited their applications in anodic electro-fermentation or cathodic electro-fermentation. Although addition of redox mediators or surfactants could promote indirect EET and regenerate intracellular reduce equivalents [ 46 , 65 ], their inhibition on the cell growth would be hazard for practical applications. Lastly, to achieve efficient coupling of inward electrons with cell growth and metabolic pathways is a bottleneck in the development of EF.…”
Section: Discussionmentioning
confidence: 99%
“…Geng et al recently introduced Tween 80 into a Zymomonas mobilis -inoculated bioelectrochemical system and accelerated the electricity generation and ethanol production simultaneously. Tween 80 was used as a surfactant to enhance the permeability cell membranes and transport of various electron shuttles across cell membranes [ 46 ].…”
Section: Unbalanced Fermentation (Anodic Electro-fermentation)mentioning
confidence: 99%
“…mobilis is supposed to be a suitable candidate for the microbial cell factory because of its remarkable ethanol productivity and potential electro-activity. 10,11 It metabolizes sugar through the Entner−Doudoroff (ED) pathway with less ATP generated for less biomass accumulation. Because ATP is dissipated predominantly during growth for intracellular energy homeostasis, more sugar diverted to the ethanol production pathway achieves a superior ethanol yield and productivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13−15 Interestingly, Z. mobilis has recently been identified as a potential electroactive bacterium due to the incomplete electron-transfer chain in the membrane, which comprises an active branched respiratory chain with type II NADH (nicotinamide adenine dinucleotide) dehydrogenase, coenzyme Q10, cytochrome bd, several c-type cytochrome terminal oxidases, and some minor or still unidentified constituents. 11 Geng et al first reported that Z. mobilis performed electrical activity and generated electricity along with ethanol production when using glucose as the primary substrate. 11 The output of electrons from Z. mobilis might imply the feasibility of using extra electrons from electrodes to regulate the cell metabolic flux in EFS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For this reason, most of the energy is expended on ethanol production rather than cell biomass thereby producing a 2.5‐fold higher substrate conversion rate than S. cerevisiae (Kang & Lee, 2015; Qiu et al, 2020; Willey, Sherwood, & Woolverton, 2017). However, S. cerevisiae is a preferred choice for industrial fermentation due to its reduced purification cost as the low pH of yeast fermentation provides higher sterility of the process which is disadvantaged to Z. mobilis (Fuchino et al, 2020; Geng et al, 2020). Clostridium sp.…”
Section: Introductionmentioning
confidence: 99%